An Unrecognized Problem in Optimizing Antimicrobial Therapy: Significant Residual Volume Remaining in Intravenous Tubing With Extended-Infusion Piperacillin–Tazobactam. (April 2023) - Peyko, Vincent
The fundamental process of medication therapy is that a medication is ordered, verified, and entirely administered to the patient. An unrecognized phenomenon across the antimicrobial landscape may be residual volume remaining within intravenous tubing, never getting to the patient. Evidence suggests that 40–60% of an antimicrobial may remain in the intravenous tubing. Across the globe, residual volume may be affecting thousands to millions of patients receiving antimicrobials each year. While residual volume may be profound for all antimicrobials, the challenges to remedy this problem are more imposing with extended-infusion administration techniques. The purpose of this article is to highlight residual volume as a potential problem in optimizing extended-infusion antimicrobial therapy with agents like piperacillin–tazobactam. Furthermore, to emphasize that recognizing this issue for antimicrobials and other medications is imperative for providers to assure every patient is receiving the medication ordered, in its entirety, to avert medication errors and optimize patient care.